2000
DOI: 10.1111/j.1540-5915.2000.tb01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning in Global Purchasing: A Model and Test of Internal Users and Corporate Buyers*

Abstract: This research examines a model centered on organizational learning in purchasing. Two different studies are conducted to test the hypotheses among purchasing users (Study 1) and buyers (Study 2). The user sample consists of users representing 355 strategic business units of a Fortune 500 multinational corporation. The buyer sample consists of corporate buyers of 200 multinational corporations drawn from the membership directory of the National Association of Purchasing Management (NAPM). In each study, the foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
227
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(241 citation statements)
references
References 59 publications
(55 reference statements)
8
227
0
1
Order By: Relevance
“…Given the boundary spanning function of purchasing towards the supply base of the firm, knowledge scanning is a key dynamic capability related to strategic purchasing (Hult et al, 2000(Hult et al, , 2006. We anticipate the positive effect of these two dynamic capability enablers in all organizational settings (i.e.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Given the boundary spanning function of purchasing towards the supply base of the firm, knowledge scanning is a key dynamic capability related to strategic purchasing (Hult et al, 2000(Hult et al, , 2006. We anticipate the positive effect of these two dynamic capability enablers in all organizational settings (i.e.…”
Section: Introductionmentioning
confidence: 93%
“…The boundary spanning and knowledge channeling nature of strategic purchasing (Hult et al, 2000;Zhang et al, 2011) may allow such involvement to be translated into dynamic capabilities and in turn improved performance (Grant, 1996;Teece et al, 1997). Yet, the impact of the change in purchasing's role on dynamic capability development and deployment remains empirically underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural equation models came up in the field, but have not been the first choice methodology in purchasing research (e.g. Fawcett & Scully, 1998;Petersen et al, 2000;Hult, Hurley, Giunipero, & Nichols, 2000;Skarmeas, Katsikeas, & Schlegelmilch, 2002;Ha, Karande, & Singhapakdi, 2004). Most papers still focused on descriptive analysis techniques.…”
Section: Research Designs and Data Analysis Techniquesmentioning
confidence: 99%
“…Oral communication capability has three dimensions: the ability to pass on information, the ability to persuade and the ability to listen and understand (Large 2006). Hult et al (2000) suggested that there is a positive relationship among organisational learning, information processing and the cycle time of the purchasing process. These results highlight the importance of dealing with communication skills and its components.…”
Section: Introductionmentioning
confidence: 99%